search
Log In
Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true
1 vote
68 views

For a sequence of real numbers $x_{1}, x_{2}, \dots , x_{n},$ if $x_{1} – x_{2} + x_{3} – \dots + (-1)^{n+1} x_{n} = n^{2} + 2n$ for all natural numbers $n,$ then the sum $x_{49} + x_{50}$ equals

  1. $2$
  2. $-2$
  3. $200$
  4. $-200$
in Quantitative Aptitude 2.7k points 5 79 342
retagged by
68 views

1 Answer

1 vote

Given that, $x_{1},x_{2},\dots, x_{n}\in \mathbb{R}$

And, $x_{1} – x_{2} + x_{3} –\dots + (-1)^{n+1}x_{n} = n^{2}+2n\quad \longrightarrow(1)$

Now, put the $n=49 \; \text{and} \; n=50,$ we get

  • $x_{1} – x_{2} + x_{3} –\dots +x_{49} = 49^{2}+2 \times 49\quad \longrightarrow(2)$

  • $x_{1} – x_{2} + x_{3} –\dots +x_{49} – x_{50} = 50^{2}+2 \times 50\quad \longrightarrow(3)$

Subtract equation $(3)$ from equation $(2).$

 $x_{1} – x_{2} + x_{3} –\dots +x_{49} – (x_{1} – x_{2} + x_{3} –\dots +x_{49} – x_{50}) = 49^{2}+2 \times 49 – (50^{2}+2 \times 50)$

$\Rightarrow x_{50} = 49^{2} – 50^{2} + 2 \times 49 – 2 \times 50$

$\Rightarrow x_{50} = (49+50)(49–50) + 2 (-1) \quad {\color{Green} {[\because a^{2} – b^{2} = (a-b)(a+b)]}}$

$\Rightarrow x_{50} = -99-2$

$\Rightarrow \boxed{x_{50} = -101}$

Now, put $n=48,$ in the equation $(1).$  

$x_{1} – x_{2} + x_{3} –\dots +x_{47} – x_{48} = 48^{2}+2 \times 48\quad \longrightarrow(4)$

Subtract equation $(4)$ from equation $(2).$

$x_{1} – x_{2} + x_{3} –\dots -x_{48} +x_{49} -(x_{1} – x_{2} + x_{3} –\dots -x_{48}) = 49^{2}+2 \times 49–48^{2} –2 \times 48$

$\Rightarrow x_{49} = 49^{2} – 48^{2} + 2 \times 49 – 2 \times 48$

$\Rightarrow x_{49} = (49+48)(49-48)+2(49-48)$

$\Rightarrow x_{49} = 97+2$

$\Rightarrow \boxed{x_{49} = 99}$

$\therefore$ The sum $\; x_{49}+x_{50} = 99-101 = -2.$

Correct Answer $:\text{B}$

10.1k points 4 8 30
edited by
Answer:

Related questions

1 vote
1 answer
1
44 views
Consider the pair of equations: $x^{2} – xy – x = 22$ and $y^{2} – xy + y = 34.$ If $x>y,$ then $x – y$ equals $7$ $8$ $6$ $4$
asked Jan 20 in Quantitative Aptitude soujanyareddy13 2.7k points 5 79 342 44 views
1 vote
1 answer
2
74 views
Anil, Bobby and Chintu jointly invest in a business and agree to share the overall profit in proportion to their investments. Anil's share of investment is $70 \%.$ His share of profit decreases by $₹ \; 420$ if the overall profit goes down from $18 \%$ to $15 \%.$ Chintu's share of ... goes up from $15 \%$ to $17 \%.$ The amount, $\text{in INR},$ invested by Bobby is $2400$ $2200$ $2000$ $1800$
asked Jan 20 in Quantitative Aptitude soujanyareddy13 2.7k points 5 79 342 74 views
1 vote
1 answer
3
81 views
If a rhombus has area $12 \; \text{sq cm}$ and side length $5 \; \text{cm},$ then the length, $\text{in cm},$ of its longer diagonal is $\sqrt{13} + \sqrt{12}$ $\sqrt{37} + \sqrt{13}$ $\frac{\sqrt{37} + \sqrt{13}}{2}$ $\frac{\sqrt{13} + \sqrt{12}}{2}$
asked Jan 20 in Quantitative Aptitude soujanyareddy13 2.7k points 5 79 342 81 views
1 vote
1 answer
4
73 views
The number of ways of distributing $15$ identical balloons, $6$ identical pencils and $3$ identical erasers among $3$ children, such that each child gets at least four balloons and one pencil, is
asked Jan 20 in Quantitative Aptitude soujanyareddy13 2.7k points 5 79 342 73 views
1 vote
1 answer
5
47 views
For a real number $x$ the condition $|3x – 20| + |3x – 40| = 20$ necessarily holds if $9 < x < 14$ $6 < x < 11$ $7 < x < 12$ $10 < x < 15$
asked Jan 20 in Quantitative Aptitude soujanyareddy13 2.7k points 5 79 342 47 views
...